Doing and undoing femininities: An intersectional analysis of young women's smoking. (November 2017) - Triandafilidis, Zoi; Ussher, Jane M; Perz, Janette; Huppatz, Kate
Previous research has found that young women's smoking relates to their performance of feminine gender identities. Using an intersectional approach, we explore in this study how young women's smoking is implicated in the doing and undoing of femininities, as well as other intersecting identities. Discourse analysis was used to examine interviews and a photography activity conducted with young women, both current and ex-smokers. This analysis revealed four culturally dominant repertoires: "cigarettes and smoking styles as gendered", "smoking as controlling weight", "smoking as a sexual tool", and "smoking as compromising appearance". Young women's experiences and negotiations of discourse surrounding smoking and femininity were shaped by intersecting social class and sexual identities. These findings can be used to inform the development of smoking cessation interventions which recognise the diversity in how young women perform femininity.